Legal Protection against Patent and Intellectual Property Rights Violations Amidst COVID-19 - Wachiraporn Poungjinda; Shubham Pathak; Ivan Bimbilovski (Emerging Science Journal, 2023)
The concept of legal principles for intellectual property (IP) protection is related to the adequate marketing of drug patents to protect patent rights. The objective of this research is to understand and analyze the factors affecting the market concerning international law, treaties, acts, and declarations, leading to encouraging creativity, production, increased investment, especially amidst the COVID-19 pandemic. The qualitative methodology provided for an in-depth understanding and analysis of primary and secondary research data gathered from key informant interviews and published literature. The collected data were analyzed with Strength, Weakness, Opportunity, and Threats (SWOT), a Delphi panel, and Correct, Adapt, Maintain, and Explore (CAME) analysis. The results found legal problems concerning the lack of rules to protect the rights and freedoms damaged by the monopoly on drug patents, complexities in the process of importing medicinal compounds, and how to access information with limited accessibility during COVID-19. Therefore, it is advisable to amend the law to curtail monopolies and to enact a law that prescribes rules for importing medicinal compounds to produce generic drugs in the country, including identifying the status of the patent holders. The research further paves the way for utilizing micro level research to be conducted in the development of intellectual property rights. Doi: 10.28991/ESJ-2023-SPER-016 Full Text: PDF